(untitled) (International Journal of Nursing Education, 2024)
A Cross-sectional study to assess the level of Parental stress and coping strategies among Mothers attending Postnatal Areas of GMCH Sector-32, Chandigarh was carried out in full compliance with ethical standards provided by the Research and Ethical committee of GMCH-32, Chandigarh. The approval was taken to conduct research from the committee of the institution. The objectives of the study were to assess the level of Parental stress among Mothers attending Postnatal Areas of GMCH Sector-32, Chandigarh, to assess the coping strategies of Mothers attending Postnatal Areas of GMCH Sector-32, Chandigarh, To find out the association of Parental stress with selected socio-demographic variables. Data was collected by using parental stress scale and self-efficacy scale from 100 study subjects from Postnatal Areas (labour room, postnatal ward and immunization).The sampling technique used was convenience sampling .The study concluded that 55% of the mothers were suffering from moderate stress, 19% were having severe stress and 26% mothers were having mild stress.16% mothers were having low level coping, 60% were having medium level coping and 24% mothers had high level of coping. Thus moderate amount of stress and medium level of coping were found to be more in Postnatal mothers. Association between parental stress and gravida of mother was found to be significant with p value =0.05 .